Efficient Votes Storage in a Non-Interactive Dining Cryptographers (NIDC) Protocol - García, Pablo (2017)
This paper shows the behavior of a storage technique for anonymous data, based on parallel channels implementation. At the beginning, it was conceived to apply on electronic vote. However, it may be generalized to whatever situation that requires anonymity and demands very high level of security respect from loss of information. Furthermore, a formula mistake that was slipped in previous publications has been corrected here. Finally, results of simulations are shown, to analyze the behavior of the equations proposed.